Sense of coherence over time for parents with a child diagnosed with cancer - Bergh Ingrid; Björk Maria (BMC, 2012)
Abstract Background When a child is diagnosed with childhood cancer this creates severe stress in the parents. The aim of the study was to describe the sense of coherence and its change over time in a sample of parents of children diagnosed with cancer. Methods The Swedish version of SOC (29 items) was used to measure the parents' (n = 29) sense of coherence. Data were collected at four time-points: Time-point 1 at the time of diagnosis; time-point 2 during the treatment; time-point 3 after the child had completed their treatment and time-point 4 when the child had been off treatment for some years or had died. Results The results showed that SOC in the investigated population is not stable over time. The parents decreased in total SOC between time-points 1, 2 and 3. Mothers had significantly weaker total SOC score including the components Manageability and Meaningfulness at time-points 1 as well time-point 2 compared to the fathers. However, for the component Comprehensibility no significant differences were shown between mothers and fathers. This study indicates that mothers' and fathers' SOC scores change over time during the child's cancer trajectory. However, the pattern in these changes varies between mothers and fathers. Conclusions This study indicates that mothers and fathers may have different support needs during their child's cancer trajectory.